1995
DOI: 10.4315/0362-028x-58.2.139
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiological Quality of Raw Cow's Milk at Collection Centers in Trinidad

Abstract: The microbial quality, pH and presence of selected pathogens in milk at eight collection centers in Trinidad were determined. The enterotoxigenicity and susceptibility of Staphylococcus aureus strains to antimicrobial agents and bacteriophages were investigated while the antibiograms and ability of Escherichia coli isolates to agglutinate O157 antiserum were also assessed. Of the 287 milk samples tested, the mean pH was 6.80 ± 0.10 and 207 (72.1%) were California mastitis test (CMT) positive. All (100.0%) milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 0 publications
4
37
3
1
Order By: Relevance
“…However, the rate of isolation of the organism was very much lower than (40%) reported from other tropical countries (Umoh et. al., 1990 andAdesiyun et. al., 1995).…”
Section: Resultsmentioning
confidence: 99%
“…However, the rate of isolation of the organism was very much lower than (40%) reported from other tropical countries (Umoh et. al., 1990 andAdesiyun et. al., 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The modified Gompertz model is expressed as (1) where N t is the bacterial cell number at time t(h), A is the initial cell number of the pathogens, C is the difference between the upper asymptotic line of the growth curve and the lower asymptotic line, B is the relative growth rate at time M, and M is the time at which the growth rate is maximum (h). Maximum specific growth rate (µ max ; Log CFU/ml/h), lag phage duration (LPD; h), and N max (Log CFU/mL) were calculated by following equations (2) where e is 2.7182, and…”
Section: Primary Model Developmentmentioning
confidence: 99%
“…For this reason, milk has received much attention, because it may serve as a vehicle for disease agents (Klein, 1901). In fact, raw milk often contains microorganisms that may cause food-borne diseases (Adesiyun et al, 1995;Headrick et al, 1998;Steele et al, 1997). Therefore, in most countries, restrictions and legislation regulating the marketing of unpasteurized milk have been introduced to minimize health risks associated with milk products (European Commission, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Unless data were to become available to prove to the contrary, it seems realistic to assume that milkborne diseases are probably at least as prevalent in South Africa as in other countries under conditions of industrialised mass production and distribution of raw and pasteurised dairy products. Surveys conducted on raw milk samples in other developing countries showed that on the whole the quality was bad [1][2][3][4]26,28,29 . As a result of the deregulation of the South African dairy industry in the early 1990's, 'milk-shops' have become a common retail outlet for milk which would not qualify for sale to large national distributors, especially in the lower socio-economic areas.…”
Section: Introductionmentioning
confidence: 99%